Akuntabilitas Pengelolaan Alokasi Dana Desa Di Desa Ledokombo Kecamatan Ledokombo Kabupaten Jember Tahun 2015 - Alwan Sri Kustono; Putri Purnamasari; Djoko Supatmoko (UPT Penerbitan Universitas Jember, 2017)
The autonomy implementation for the village will be the village government is power to administer, regulate and to conduct their own household based on the principle of transparency (openness) and accountability (responsibility). The accountability includes planning, action, administration, reporting and responsibility. Each stage of the management process has rules that must be understood and implemented in a settled period of time. But there are new problems when the village accountability is required to be managed in a transparent, accountable and participatory way, the execution somehow does not coincide with the village functionaries and dwellers' preparedness in implementing the process. The unpreparedness is caused by the limited capacity and quality of the human resources in managing the Village Fund Allocation. This study was conducted by using descriptive analysis along with qualitative approach to determine the accountability in the management of the Village Fund Allocation in Ledokombo village, and the factors that can inhibit and support the management process. In addition, the data collection method that was applied was triangulation technique with interview, observation and documentation. The results of this study showed that the planning, implementation, reporting, and accountability had been implemented well although there were still some procedures that had not been apt in terms of time allocation in the implementation process such as some issues in writing accountability documents and overdue delivering system.Keywords: Accountability,Village Fund Allocation,Financial Management village.